2020
DOI: 10.1111/cjag.12222
|View full text |Cite
|
Sign up to set email alerts
|

The impact of customer ratings on consumer choice of fresh produce: A stated preference experiment approach

Abstract: The importance of customer ratings or reviews in online shopping has been recognized in the previous literature; however, few have studied how online customer rating scores affect consumers’ fresh produce purchases and its importance relative to other fresh produce attributes. The quality of fresh produce demonstrates high uncertainty and variation; therefore, the impact of user‐generated content such as customer rating scores on the choice of fresh produce may be more complex than on other product categories.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 52 publications
2
17
2
Order By: Relevance
“…The perception that local food is fresher, healthier, environmentally friendly, and more sustainable mainly drive the popularity of local foods (Curtis & Cowee, 2011; Fernqvist & Ekelund, 2014). Although many studies on local food exist, most of them have only examined the impact of locality as a credence attribute using survey or experimental auction methods (Darby et al, 2008; He et al, 2020; Hu et al, 2012; Jekanowski et al, 2000; Loureiro & Umberger, 2003; Weatherell et al, 2003). However, in the actual grocery store shopping, consumers can obtain various types of attribute information, such as color, size, and shape.…”
Section: Discussionmentioning
confidence: 99%
“…The perception that local food is fresher, healthier, environmentally friendly, and more sustainable mainly drive the popularity of local foods (Curtis & Cowee, 2011; Fernqvist & Ekelund, 2014). Although many studies on local food exist, most of them have only examined the impact of locality as a credence attribute using survey or experimental auction methods (Darby et al, 2008; He et al, 2020; Hu et al, 2012; Jekanowski et al, 2000; Loureiro & Umberger, 2003; Weatherell et al, 2003). However, in the actual grocery store shopping, consumers can obtain various types of attribute information, such as color, size, and shape.…”
Section: Discussionmentioning
confidence: 99%
“…First, the study did not take into account other attributes of Fuji apples, such as color, freshness, taste, brand, and labeling. However, studies have shown that these attributes also influence consumers’ preference and WTP for fresh products (e.g., Wang and Huo, 2016 ; He et al, 2020 , 2021 ; DeLong et al, 2021 ; Tanemura and Hamadate, 2022 ; Wang et al, 2022 ). Second, our sample was limited to consumers only in six cities in China, so a future study may cover a wider range of urban consumers nationwide to conduct more robust tests.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies mainly focus on UGC (e.g. He et al , 2020) because it acts as an effective source of word of mouth and an indicator of product quality (Kumar et al , 2016). As firms increasingly depend on social media, marketers attach great importance to generate content.…”
Section: Literature Reviewmentioning
confidence: 99%